The Impact of Authority on Reporting Behavior, Rationalization and Affect - Mayhew, Brian W.; Murphy, Pamela R. (Contemporary Accounting Research, 2014)
Appendix S1. Instructions: Part I Appendix S2. Instructions: Part 2 Please note: The publisher is not responsible for the content or functionality of any supporting information supplied by the authors. Any queries (other than missing content) should be directed to the corresponding author for the article.